2010
DOI: 10.1007/s10570-010-9425-7
|View full text |Cite
|
Sign up to set email alerts
|

The glass transition and crystallization of ball milled cellulose

Abstract: Samples of ball milled cellulose were prepared by ball milling pulps from eucalyptus and softwood (spruce/pine). Water sorption isotherms were obtained by both dynamic vapor sorption and equilibration over saturated salt solutions, in the water content range of 5-42% db (db = dry basis; water as a % age of total solids). Dynamic mechanical analysis using a pocket technique showed a water content dependent thermal transition occurring at the same temperature for the two pulp samples, which was interpreted as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 45 publications
6
37
1
6
Order By: Relevance
“…ball milling treatments. This result is in contrast to those reported in some of the literatures 31,32,48 where the authors report that the celluloses converted into amorphous celluloses or cellulose II by ball milling technique. Ciolacu et al reported that the ball milled cellulose regenerated in ethanol does show any peak corresponding to planes 101, 101, and 002.…”
Section: X-ray Diffraction Studiescontrasting
confidence: 99%
“…ball milling treatments. This result is in contrast to those reported in some of the literatures 31,32,48 where the authors report that the celluloses converted into amorphous celluloses or cellulose II by ball milling technique. Ciolacu et al reported that the ball milled cellulose regenerated in ethanol does show any peak corresponding to planes 101, 101, and 002.…”
Section: X-ray Diffraction Studiescontrasting
confidence: 99%
“…8. Paes et al 2010). The soluble sample only shows a broad peak, which is characteristic of amorphous lignin.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 96%
“…Ash content was measured following the NREL method (Sluiter et al 2005), and it was 2.13%. The hydrolysis lignin was dried in an oven at 105 °C for 12 h. The material was ground in a planetary ball mill (Retsch PM100) at 200 rpm for 24 h. This rate is low enough to preserve the crystallinity of cellulose (Paes et al 2010), which might be present in the sample as an impurity. The milled lignin was sieved to obtain two samples with different particle size.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Nanocellulose was prepared through ball-milling process [5] and hydrolysis method in previous studies [6]. However, mechanical method has the shortcoming of high energy consumption and low production efficiency [7].…”
Section: Introductionmentioning
confidence: 99%